ANALISIS SELISIH REALISASI RETRIBUSI DAN PAJAK DAERAH PEMERINTAH DI KABUPATEN KEPULAUAN TALAUD - Luntungan, Haryo P.; Sabijono, Harijanto; Pusung, Rudy J. (Universitas Sam Ratulangi, 2019)
The inability to extract regional sources of income will impact on financing regional development. Locally-generated revenue is the backbone of development, if does not increase it is feared that it will disrupt the wheels of development. To know ability of the Talaud Regency Government to explore receipts ofÂ Regional Retribution and Regional Taxesby determining budget of tax collection and levies will know the final results of the realization of the collection of taxes and levies, it will be seen that the comparison shows the effectiveness of Regional Taxes and Regional Levies. The aim of the study was to find out the magnitude change in difference, and analyze effectiveness of Regional Retribution and Regional Taxes on Original Local Government Revenue Talaud island district. data analyzed are budget data and realization Regional Retribution and Regional Taxes during 2012-2017. Data analysis tool used is the difference analysis and effectiveness analysis. This type of research is conducted using qualitative descriptive research.The results of the difference analysis both for Regional Retribution and Regional Taxes for 2012-2017 are more differences between realization and budget. For the level of effectiveness of regional Retribution and regional taxes, there are those that are not effective until very effective, because the calculation results are less than 60% to above 100%. The Regional Tax Management Agency and the Regional Retribution of the Talaud Islands Regency should need communication and good relations or good cooperation between the collecting parties and the community.